2019
DOI: 10.1097/md.0000000000014304
|View full text |Cite
|
Sign up to set email alerts
|

How international are the editorial boards of leading spine journals? A STROBE-compliant study

Abstract: Low- and middle-income countries contribute to only a small percentage of publications in multiple medical fields. Editorial bias was reported to be an important reason for this. However, whether this trend exists in leading spine journals remains unclear. This study determined the composition of the editorial boards of leading spine journals and analyzed the international representation of editorial boards. The editorial board members of four leading subspecialty spine journals, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(53 citation statements)
references
References 22 publications
(61 reference statements)
2
51
0
Order By: Relevance
“…[15] A survey indicates that researchers from LAMIC believe that a biased attitude of editors from high-income countries (HIC) against their work may lead to the under-representation of LAMIC authors in publications. [19] The under-representation of editors from LAMIC was also found in multiple medical fields, [20][21][22][23] such as pharmacy, [6] psychiatry, [13] spine, [14] and neurology. [9] However, whether this phenomenon exists in the field of foot and ankle surgery is remain unknow.…”
Section: Introductionmentioning
confidence: 99%
“…[15] A survey indicates that researchers from LAMIC believe that a biased attitude of editors from high-income countries (HIC) against their work may lead to the under-representation of LAMIC authors in publications. [19] The under-representation of editors from LAMIC was also found in multiple medical fields, [20][21][22][23] such as pharmacy, [6] psychiatry, [13] spine, [14] and neurology. [9] However, whether this phenomenon exists in the field of foot and ankle surgery is remain unknow.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are consistent with prior studies that have revealed substantial underrepresentation of editorial staff members of major biomedical journals who are affiliated with LMICs. 9 , 10 , 11 , 12 , 19 , 20 One 2005 study reported that 96% of editorial staff members of leading pediatric journals were based in HICs, 21 and another study in 2014 reported that 93% of editorial staff members of leading orthopedics journals were based in HICs. 9 Similarly, in 2020, we found that 95% of the cumulative total of editorial staff members in the selected journals with high impact factors across various fields were based in HICs.…”
Section: Discussionmentioning
confidence: 99%
“…Lesser academic incentive for publication outside the U.S. and India, if present, may also contribute to publication disparities. If editorial boards of peerreviewed journals are not of diverse national origin, the composition of persons selecting manuscripts for publication may also contribute to publication disparities (42)(43)(44). Fees for publication may contribute to disparities in publication (45), although this does not explain disparately low numbers of publications out of the United Kingdom or other HICs: although some journals waive their fee for publication for LMICs (46,47), authors may not know this, and may therefore perceive a financial barrier to publication.…”
Section: Discussionmentioning
confidence: 99%